Contextual numeracy skills in elementary school: diagnostic profile using AKM-based numeracy test and PISA framework - Siti Nurul Koimah; Fara Virgianita Pangadongan; Fitri Aida Sari; Sukriadi Sukriadi; Sri Lestari (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Contextual numeracy is an essential competency for applying mathematical knowledge in real-life situations; however, its empirical profile among elementary school students in Indonesia remains underexplored. This study aimed to describe the contextual numeracy skills of fifth-grade elementary school students based on the PISA cognitive process domains, namely Formulate, Employ, and Interpret/Evaluate, as well as five situational contexts: personal, occupational, societal, scientific, and cultural. A quantitative descriptive design was employed involving 56 students from two fifth-grade classes in one elementary school in Samarinda, while another class in the same school was used for instrument tryout. The instrument was developed based on the AKM and PISA frameworks and consisted of 10 multi-format items. The instrument demonstrated strong content validity (CVI = 0.92) and good reliability (Cronbach’s alpha = 0.81). The results showed that students’ contextual numeracy skills were generally low, with a mean score of 3.96 out of 10. Among the cognitive process domains, Employ showed the highest achievement, while Formulate and Interpret/Evaluate showed lower achievement. Higher performance also appeared on societal items than on personal and occupational items. However, these differences should be interpreted in light of the study design and the limited and uneven representation of items across contexts and formats. The findings provide a local diagnostic profile that may support more targeted context-based mathematics learning in elementary school settings.